2019
DOI: 10.1158/0008-5472.can-18-1326
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Glycolysis and Reductive Carboxylation of Glutamine Potentiates Activity of Oncolytic Adenoviruses in Cancer Cells

Abstract: Tumor cells exhibiting the Warburg effect rely on aerobic glycolysis for ATP production and have a notable addiction to anaplerotic use of glutamine for macromolecular synthesis. This strategy maximizes cellular biosynthetic potential while avoiding excessive depletion of NAD þ and provides an attractive anabolic environment for viral infection. Here, we evaluate infection of highly permissive and poorly permissive cancer cells with wild-type adenoviruses and the oncolytic chimeric adenovirus enadenotucirev (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 45 publications
2
41
1
1
Order By: Relevance
“…Another study compared the effects of infection with HAdVC-5, wild-type HAdV species B type 11p (HAdVB-11p) (Table 1), and an oncolytic HAdV, enadenotucirev (EnAd, formerly ColoAd1), on metabolism of A549 cells (Table 2) and SKOV3 ovarian carcinoma cells (Table 2) [45]. HAdV infection increased glycolysis and glutaminolysis [45], as expected [25,26,46,47]. However, counterintuitively, the authors found that inhibiting glycolysis with 2-deoxyglucose (2DG) or limiting glucose availability increased viral genome replication and packaging efficiency in both A549 cells and SKOV3 cells [45].…”
Section: Metabolomic and Proteomic Analyses Of Adenovirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study compared the effects of infection with HAdVC-5, wild-type HAdV species B type 11p (HAdVB-11p) (Table 1), and an oncolytic HAdV, enadenotucirev (EnAd, formerly ColoAd1), on metabolism of A549 cells (Table 2) and SKOV3 ovarian carcinoma cells (Table 2) [45]. HAdV infection increased glycolysis and glutaminolysis [45], as expected [25,26,46,47]. However, counterintuitively, the authors found that inhibiting glycolysis with 2-deoxyglucose (2DG) or limiting glucose availability increased viral genome replication and packaging efficiency in both A549 cells and SKOV3 cells [45].…”
Section: Metabolomic and Proteomic Analyses Of Adenovirus Infectionmentioning
confidence: 99%
“…HAdV infection increased glycolysis and glutaminolysis [45], as expected [25,26,46,47]. However, counterintuitively, the authors found that inhibiting glycolysis with 2-deoxyglucose (2DG) or limiting glucose availability increased viral genome replication and packaging efficiency in both A549 cells and SKOV3 cells [45]. Inhibition of glycolysis in SKOV3 cells, which, unlike A549 cells, exhibit a metabolic phenotype that does not resemble the Warburg effect [65], also increased the speed of EnAd and HAdVB-11p viral replication and progeny production [45].…”
Section: Metabolomic and Proteomic Analyses Of Adenovirus Infectionmentioning
confidence: 99%
“…Its reported that interfering with cancer cells metabolism through glycolysis inhibition may enhance oncolytic virotherapy activity [27]. A recent study showed that using 2-deoxyglucose (2DG) to block glycolysis or through restricting glucose amount will enhance oncolytic adenoviruses activity in permissive and poorly permissive cancer cells [28]. Furthermore, pyruvate dehydrogenase kinase inhibition showed to improve reovirus oncolytic anti-tumor efficacy in several cancer types [29].…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of immune checkpoints, immunogenic chemotherapy and IFN-α suppression can promote the local therapeutic effect of oncolytic viruses by direct intratumoral injection (41). Antagonizing the glycolysis and carboxylation of glutamine can enhance the activity of an oncolytic adenovirus directly injected into tumors by promoting its lysis in the cancer cells (49).…”
Section: Direct Intratumoral Deliverymentioning
confidence: 99%